2015
DOI: 10.1590/1679-78251470
|View full text |Cite
|
Sign up to set email alerts
|

Stress Analysis of Laminated Composite and Sandwich Beams using a Novel Shear and Normal Deformation Theory

Abstract: A novel Normal and Shear Deformation Theory (NSDT) for analysis of laminated composite and sandwich beams, taking into account shear deformation as well as normal deformation, is developed. The paper investigates flexural behaviors of thick laminated and sandwich beams under plane stress conditions using NSDT. A generalized displacement-based refined formulation is elucidated with inclusion of various warping functions in terms of thickness coordinates to represent shear and normal deformation effects. These e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
1
8
0
1
Order By: Relevance
“…It should be noted that normal and shear deformation effects are included in these studies with different models. Again, excellent agreement with previous studies can be observed, especially with those from Pawar et al [20]. As beam gets thinner, the present results agree well with those of Carrera et al [29] for various boundary conditions.…”
Section: Numerical Examplessupporting
confidence: 93%
See 2 more Smart Citations
“…It should be noted that normal and shear deformation effects are included in these studies with different models. Again, excellent agreement with previous studies can be observed, especially with those from Pawar et al [20]. As beam gets thinner, the present results agree well with those of Carrera et al [29] for various boundary conditions.…”
Section: Numerical Examplessupporting
confidence: 93%
“…They have not been reported before and could be served as benchmark examples for future references. The results are also compared with those from Kant et al [19] and Pawar et al [20] and Carrera et al [29]. It should be noted that normal and shear deformation effects are included in these studies with different models.…”
Section: Numerical Examplesmentioning
confidence: 93%
See 1 more Smart Citation
“…In the FOBT, a constant state of transverse shear strain is assumed that does not satisfy the zero shear stress condition at the top and bottom edges of the beam and thus requires a shear correction factor to compensate for this error (see, e.g., Wang et al, 2000;Eisenberger, 2003;Civalek and Kiracioglu, 2010;Lin and Zhang, 2011;Endo, 2016). In general, the HOBTs adopt a specific function (parabolic, trigonometric, exponential, or hyperbolic) to more accurately represent the shear stress distribution along the beam's thickness and do not require the shear correction factor (see e.g., Reddy, 1984;Heyliger and Reddy, 1988;Khdeir and Reddy, 1997;Murthy et al, 2005;Vo and Thai, 2012;Pawar et al, 2015;Nguyen et al, 2017;Srinivasan et al, 2019). The literature contains a plethora of publications on the subject, and the interested reader is referred to the excellent review paper of Liew et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…Carrera bileşik fonksiyonu ile tabakalı kompozitlerin normal/kayma gerilmeleri elde edilmiştir [24]. Kompozit kirişlerin normal ve kayma gerilmeleri için normal ve kayma deformasyon teorisi geliştirilmiştir [25]. Dik açılı kompozit kirişlerin kesit boyunca normal ve kayma gerilmeleri için yüksek mertebeden kayma deformasyon teorisi önerilmiştir [26].…”
Section: Introductionunclassified